2016
DOI: 10.1051/parasite/2016006
|View full text |Cite
|
Sign up to set email alerts
|

A review of the proposed role of neutrophils in rodent amebic liver abscess models

Abstract: Host invasion by Entamoeba histolytica, the pathogenic agent of amebiasis, can lead to the development of amebic liver abscess (ALA). Due to the difficulty of exploring host and amebic factors involved in the pathogenesis of ALA in humans, most studies have been conducted with animal models (e.g., mice, gerbils, and hamsters). Histopathological findings reveal that the chronic phase of ALA in humans corresponds to lytic or liquefactive necrosis, whereas in rodent models there is granulomatous inflammation. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 127 publications
(182 reference statements)
0
20
0
1
Order By: Relevance
“…Neutrophils have been implicated in defense against this parasite playing a crucial protective role (Asgharpour et al, 2005 ); nevertheless, involvement of neutrophils and other leukocytes in tissue damage has also been reported (Olivos-García et al, 2007 ). Oxidative (ROS production) and non-oxidative mechanisms are proposed to be used by neutrophils to kill amoeba (Ghosh et al, 2010 ; Pacheco-Yépez et al, 2011 ; Campos-Rodríguez et al, 2016 ). Mechanisms triggering neutrophils by amoebas are unknown but they could involve innate immune receptors such as TLRs.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils have been implicated in defense against this parasite playing a crucial protective role (Asgharpour et al, 2005 ); nevertheless, involvement of neutrophils and other leukocytes in tissue damage has also been reported (Olivos-García et al, 2007 ). Oxidative (ROS production) and non-oxidative mechanisms are proposed to be used by neutrophils to kill amoeba (Ghosh et al, 2010 ; Pacheco-Yépez et al, 2011 ; Campos-Rodríguez et al, 2016 ). Mechanisms triggering neutrophils by amoebas are unknown but they could involve innate immune receptors such as TLRs.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that the low expression of MPO in hamsters can decrease the presence of NETs (Figure 2), since this enzyme is a key element to induce the release of these traps. Some authors have suggested an important role for MPO against E histolytica , 2,11,35 and it is thought that differences in MPO concentration in the hamster and mouse can be crucial to eliminate the amoeba, since a previous work determined that MPO can be joined to the trophozoites of E histolytica and eliminate them 35 . In addition when we evaluated the amoeba viability (Figure 4) in the in vitro interactions using an MPO inhibitor (ABAH), the viability increased in comparison to that of 90‐min interaction group.…”
Section: Discussionmentioning
confidence: 86%
“…These two diseases are associated with significantly high levels of mortality worldwide 1 . Some authors have suggested that liver tissue damage observed in amoebic invasion is not directly related to amoebic mechanisms 2 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El papel de estas citoquinas en el patógeno de los abscesos hepáticos amebianos necesita más investigación, particularmente para buscar otros factores de crecimiento, como TGF-b, HGF e IGF, y citoquinas reguladoras para elucidar sus roles durante las etapas crónicas del desarrollo de AHA. Varios estudios han demostrado la importancia de los neutrófilos en la respuesta innata contra la invasión de E. histolytica (52). Los neutrófilos activados proporcionan señales para la activación y maduración de los macrófagos, que a su vez liberan IL-1b, TNF-a, G-CSF y GM-CSF, de tal forma que estas citoquinas extienden la vida útil de los neutrófilos en los sitios de inflamación.…”
Section: El Estudio De Las Citoquinas Como Ejemplo De Investigaciónunclassified